Academic Credentials, Students’ Characteristics, Decision Making Behaviour Of Malaysian Polytechnics Students And Their Educational Choice - Foo, Jyy Wei (2018)
An understanding of the decision making process of post secondary education by students is needed for administrators to successfully recruit and retain students. This study seeks to provide research findings on Malaysian polytechnics’ students educational choices regarding Technical and Vocational Education Training (TVET) in terms of enrolment programme with students’ characteristics, academic credentials and decision making behaviour. Student characteristics, academic credentials and decision making behaviour were assessed via a self-report questionnaire; data included socioeconomic status (SES), educational aspirations, performance in secondary school, availability of desired programmes, employment opportunities, satisficing, decision difficulty and alternative search.